Mastectomized woman: nursing intervention and natural killer activit - Paula Cristina de Andrade Pires Olympio; Eliane Lima; Maria Helena Costa Amorim (Universidade de Santa Cruz do Sul, 2014)
Backgound and Objectives: Psychoneuroimmunology is one of the areas in charge of nurses, as it provides the implementation of an individualized and humanistic practice, perceiving the patient as a whole and aiming at physical and psychological aspects. The objective of this study was to evaluate the activity of Natural Killer (NK) cells in women with breast cancer when the relaxation technique was used in nursing interventions and assess the association between the activity of NK cells and the pattern of behavior for stress and coping. Method: This is an experimental study with a quantitative approach, carried out with mastectomized women submitted to chemotherapy. Results: It was observed that NK cell levels, at the 1st measurement, were not statistically different between the control and experimental groups, demonstrating that the control and experimental groups were initially homogeneous. However, the same groups showed significant differences at the 2nd measurement. Conclusion: The nursing intervention using the relaxation technique modified the activity of NK cells, as the women in the experimental group showed increased activity after learning and practicing relaxation techniques.